(untitled) - Mishima, Yukio (Tokyo, Japan, 1992)
Is the world really falling apart? Is the ideal of progress obsolete? Cognitive scientist and public intellectual Steven Pinker urges us to step back from the gory headlines and prophecies of doom, and instead, follow the data: In seventy-five jaw-dropping graphs, Pinker shows that life, health, prosperity, safety, peace, knowledge, and happiness are on the rise.
Keywords: Samurai,Samurai; Conduct of life,Hành vi cuộc sống